2010
DOI: 10.1016/j.gie.2009.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive imaging of gastroesophageal biopsy samples by spectrally encoded confocal microscopy

Abstract: Background Spectrally encoded confocal microscopy (SECM) is a high-speed reflectance confocal microscopy technique that has the potential to be used for acquiring comprehensive images of the entire distal esophagus endoscopically with subcellular resolution. Objective The goal of this study was to demonstrate large-area SECM in upper GI tissues and to determine whether the images contain microstructural information that is useful for pathologic diagnosis. Design A feasibility study. Setting Gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 32 publications
(40 reference statements)
2
58
1
Order By: Relevance
“…Reflectance confocal microscopy, also known as "spectrally encoded confocal microscopy," has been used in ex vivo studies to image the GI mucosa, including the esophagus. 35 This technique uses scattered light to create images of the GI mucosa and no contrast agent is needed. This technique is an ex vivo research tool, but could potentially be developed for in vivo use in the future.…”
Section: Future Developments In Clementioning
confidence: 99%
“…Reflectance confocal microscopy, also known as "spectrally encoded confocal microscopy," has been used in ex vivo studies to image the GI mucosa, including the esophagus. 35 This technique uses scattered light to create images of the GI mucosa and no contrast agent is needed. This technique is an ex vivo research tool, but could potentially be developed for in vivo use in the future.…”
Section: Future Developments In Clementioning
confidence: 99%
“…Previously, we showed that SECM can visualize key cellular features associated with various esophageal diseases [9][10][11]. The translation of SECM into a clinically-useable endoscopic device for esophageal imaging, however, has been delayed in part by the imaging rate of our previous SECM system, 5 kHz [12].…”
Section: Introductionmentioning
confidence: 99%
“…This technique can be further expanded to other applications by stitching multiple extended FOV images together to create a large-area image. 26 Potential clinical applications include dermatological 33 and gastroesophageal 27 studies. Combined beam and stage scanning could also increase the large field of view image acquisition speed for other point scanning microscopy techniques, such as non-linear microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, spectral encoding in one axis to scan 180 μm and stage scanning in both lateral axes with mosaicing has been used to image large esophageal biopsy specimens. 27 Axial scanning of the objective lens using a piezoelectric transducer allowed three-dimensional images over a 120 to 150 μm depth range. Fields of view ranging from 2 × 1 mm 2 to 5 × 3.6 mm 2 were acquired in 2.5 to 15 minutes.…”
Section: Confocal Microscopymentioning
confidence: 99%